Study on discharge velocity of tailings mortar in dam break based on FLOW-3D. Issue 1 (January 2021) - Hu, Jiahao; Na, Chengwei; Wang, Yi
Abstract: Tailings pond is used to store the tailings discharged from the mine after separation and mining. As a potential hazard source with high potential energy, the tailings mortar with high potential energy after dam break is transformed into high-speed dynamic energy sand flow to impact the downstream area through energy conversion. In this paper, through the establishment of a three-dimensional model of a tailings pond, the FLOW-3D software is used for numerical simulation, and the influence of correlation coefficient on the discharge speed of tailings mortar after dam break is analyzed, and the relevant migration law is obtained. The test in this paper can provide a reference for the corresponding disaster and protection engineering research.